Safeguarding secrets, shaping acquisitions: Trade secret protection and the role of distance between acquirer and target - M. F. Arroyabe; Christoph Grimpe; Katrin Hussinger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
We investigate whether strengthened legal protection of trade secrets increases the likelihood of a firm being acquired. Stronger protection can make a firm more attractive for acquisition due to better safeguarding of trade secrets, but it may also increase information asymmetries that discourage potential acquirers. Using the staggered implementation of the Uniform Trade Secrets Act (UTSA) in the U.S., we show that stronger trade secret protection increases the likelihood of being acquired, but also changes firms' acquisition strategies more broadly depending on the distance between acquirer and target. Compared to domestic acquirers, foreign acquirers are only half as likely to make an acquisition, and they prefer to acquire minority rather than majority stakes. Both domestic and foreign acquirers are more likely to pursue stepwise acquisitions of a target as protection increases, consistent with a real options rationale. Further investigation suggests that, while increased trade secret protection increases information asymmetries for all acquirers, foreign acquirers as well as domestic acquirers located further away from a target are disproportionately affected.
Keywords: G34; O34; L20; 330; trade secret protection; firm acquisitions; ownership stakes; distance; Uniform Trade Secrets Act (UTSA)